Analysis of Speech Acts in Literary Novels by Tenderlova - Farisha Oktaviruni Alifa; Intan Sari Ramdhani (CV. Rayyan Dwi Bharata, 2023)
This study analyzes the speech acts in the novel entitled Literary Writing. This study aims to describe the types of speech acts found in the novel entitled Literary Writing. This research uses descriptive analysis method. The data of this research is sourced from the dialogue of the contents of the novel contained in literary novels. The data analysis technique used in this study is the reading technique and the note taking technique. The results of the analysis of this study can be seen from the objects used, namely the existence of 3 pragmatic speech acts, including: 1) locutionary speech acts, 2) illocutionary speech acts, 3) perlocutionary speech acts contained in the novel.